Fälttävlans förändring över tid med fokus på deltagande, säkerhetsarbete och skador - Nyberg, Linda; Svensson, Fanny (2020)
The change of eventing over time with focus on participation, safety and injuries Eventing is equestrians’ version of a triathlon were the cross country phase is the most challenging of the three and can result in serious injuries. Every year there are a few reported deaths due to eventing despite equestrian federations major focus on safety. The configuration of the phases included in eventing has changed over the years, but there is still a lack of knowledge as to how the historic participation has changed and what injuries are most prevalent in the sport. The aim of this study is to increase knowledge regarding the historic change of eventing with focus on participation, safety and the prevalence of injuries. Achieving this by answering the following questions; How has the participation in eventing changed in relation to the change of the sports configuration? How is the progress of safety perceived in eventing, and how has the safety’s progress affected the prevalence of injuries? What challenges is the future development of eventing facing? The questions were answered by gathering information from a number of scientifically reviewed articles, and through four qualitative interviews with people who have long experience of eventing. Women’s and children’s participation have increased over time. There were no experienced differences between how women and men were treated in eventing. Regarding the development of eventing safety, the study shows that Sweden is leading nation. Much in the eventing has become safer, above all; obstacle construction; cross country design; protective equipment. The participants in the study assessed that the same type of injuries occur today as when they started with eventing. There is a concern regarding the future of eventing due to riders leaving the sport after ending their careers without contributing back to the sport. The study concludes that the participation in eventing has changed over time, from originally male soldiers in their thirties were the only participants to now the majority of participants being females and children. There has not been maintained any visible gender systems in eventing due to men and women participate on the same terms. Safety has developed over time through clearer guidelines of course construction, deformable fences and more modern safety equipment. Injuries and deaths of eventing equipage still occurs but further studies is needed to determine to what extent the development of safety has reduced the prevalence of injuries or not. There is a concern for the future of eventing due to experienced riders leaving the sport completely, which leads to that the exchange of knowledge is lost and that the non-profit dedication fades.